PLANNING OF HISTORY TEACHING-LEARNING IN CAMEROON: INTEGRATION OF TEACHERS' BELIEFS INTO TEACHING SHEETS FOR GENERAL SECONDARY EDUCATION - Éric MENYE OBIA; Patrick MBENGUE ZE (Universitaria Publishing House, Craiova, 2021)
This article is the result of an exploratory-descriptive research carried out with 65 history teachers from Cameroon and their 130 teaching sheets by describing the integration of teacher' beliefs in the planning of history teaching-learning of history teaching-learning. It associated with the current socioconstructivism paradigm which places the learner at the center of a didactic project. It reveals that the teachers have a pseudoconstructivist pedagogical belief, an illusion of constructivist psychological beliefs, an integration of the positivist epistemological belief, an absence of the historical narrative in the pedagogical sheets. These results have implications for planning.